3,5-Dibenzoyl-2,6-Dimethyl-1-Pentyl-4-Pyridone - Şahin, Z.S.; Işík, S.; Şener, A.; Tan-Uygun, M. (Int Union Crystallography, 2009)
In the crystal structure of the title compound, C26H 27NO3O, a one-dimensional network of C - H⋯O hydrogen bonds and π-ring inter-actions is responsible for crystal stabilization. Inter-molecular hydrogen bonds and C - H⋯ π inter-actions produce R 2 2(10), R 4 4(27) and R 4 4(29) rings.